No ateliê da memória: uma análise sobre o currículo de artes de Cariacica-ES fundamentada na Educação das Relações Étnico-Raciais - Penha, Jakslaine Silva da (2023)
This master's research has as main objective to investigate how the contents related to the Education of Ethnic-Racial Relations (Erer), in especially the teaching of Afro-Brazilian and African History and Culture, are present in the Arts curriculum of the “Curriculum Guidelines of the Municipality of Cariacica - Elementary School (6th to 9th grade)”. The research is justified for two reasons, one of a practical nature and the other subjective: firstly, it starts from the perception of the relevance that fundamental education plays in the social formation of people who experience the Arts curriculum in the city of Cariacica. As a second argument, my personal perception is that, once a student of the municipal network of Cariacica, I consider the experiences lived in the school environment as motivation. It was mainly this argument that was responsible for conducting the investigation through (auto)biographical research. Given the propositions described, the study is characterized as a research with a qualitative approach. The text initially recovers, in an essayistic tone, part of my school trajectory and the strength of teaching Arts in this formation. Then, in the Introduction, it contextualizes the research topic and the methodological proposal. The other chapters are structured as follows: the first serves as a bibliographical review of a “State of knowledge” about the fields that subsidize the research: the teaching of Arts, Erer and curriculum. The next is an essay on the curriculum as a right of students and educators. Next, two chapters are dedicated to the presentation of the general structure of the “Curriculum Guidelines of the Municipality of Cariacica - Elementary School (6th to 9th grade)” and to the analysis of this document. Among the main references that make up the conceptual contribution of the dissertation are theorists such as Ana Mae Barbosa (2012), Nilma Lino Gomes (2012), Megg Rayara Gomes de Oliveira (2012), Miguel Arroyo (2013), and artists such as Ayrson Heráclito, Ione Reis, Maria Auxiliadora da Silva and Moisés Patrício. The research results, arising from the documental analysis, indicate that the Cariacica Arts curriculum deals indirectly with the teaching of Afro-Brazilian and African History and Culture and unintentionally with the National Curriculum Guidelines of Erer.